2021
DOI: 10.1177/09564624211046995
|View full text |Cite
|
Sign up to set email alerts
|

Staying, leaving and returning: Trends of prevention of mother-to-child transmission retention among newly diagnosed HIV-positive pregnant and postpartum women

Abstract: Uptake of services and retention throughout the Prevention of Mother-to-Child Transmission continuum are necessary to achieve the goal of reducing Mother-to-Child Transmission of Human Immunodeficiency Virus (HIV). Adopting a retrospective cohort design, we tracked the uptake of services in a district hospital in Ghana from antenatal booking through to six weeks postnatal when early infant diagnosis was conducted. Of the 1252 pregnant women booked antenatally, 94.1% ( n = 1178) received pre-test counselling, 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In a systematic review and meta-analysis of studies up to 2017 in Africa, 5 the pooled estimate of retention in care during pregnancy and postpartum in the Option B+ era was 74.5% (ranging from 42 to 97%) at 12 months after ART initiation (loss to follow-up was defined as more than 90 days without attending an appointment), and younger age and late ART initiation were associated with a higher loss to follow-up. More recent studies reported variable retention rates, ranging from only 67.4% 6 weeks postpartum in Ghana 6 to 85.6% at 12 months in Kenya, a rate similar to the one observed in our study. 14 Young age, no education, lack of disclosure, recent HIV diagnosis have all been shown to be associated with higher rates of loss to follow-up (LTFU) in studies focusing on determinants of retention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a systematic review and meta-analysis of studies up to 2017 in Africa, 5 the pooled estimate of retention in care during pregnancy and postpartum in the Option B+ era was 74.5% (ranging from 42 to 97%) at 12 months after ART initiation (loss to follow-up was defined as more than 90 days without attending an appointment), and younger age and late ART initiation were associated with a higher loss to follow-up. More recent studies reported variable retention rates, ranging from only 67.4% 6 weeks postpartum in Ghana 6 to 85.6% at 12 months in Kenya, a rate similar to the one observed in our study. 14 Young age, no education, lack of disclosure, recent HIV diagnosis have all been shown to be associated with higher rates of loss to follow-up (LTFU) in studies focusing on determinants of retention.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported variable rates of retention and assessed its possible determinants, but different definitions of retention were used, precluding direct comparisons and complicating the interpretation of results. 26 One important issue in evaluating retention in care is that loss to follow-up often includes silent transfers to other clinics, changes of residence, treatment interruptions, and deaths. 7 Documenting real outcomes among patients lost to follow-up is therefore important but may be difficult unless tracing strategies are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Morse [ 15 ] however suggested that, not all nurse-patient relationships are therapeutic in nature and those that are not, have negative repercussions such as disengagement from care and low acceptance of health provider’s advice [ 16 ]. Consequently, findings from the phase one of this study recorded the retention rate in the PMTCT programme in the study setting at six weeks postpartum as 67.4%, with the highest disengagement of 58.9% occurring antenatally [ 17 ]. In spite of the significant attrition rate, although it is uncertain, it is believed that positive experiences of nurse-patient relationships may have contributed to the mothers’ decision to remained in the programme.…”
Section: Introductionmentioning
confidence: 99%